2007
DOI: 10.1177/1557988307302094
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' Experience of Social Support After the Death of a Child

Abstract: The aims of this study were to describe fathers' social networks and their experience of social support after the death of a child. The sample consisted of 8 fathers who had lost a child under the age of 3. The data were collected with open-ended questions and interviews. Data analysis used qualitative content analysis. The fathers' social support networks varied over time and between fathers. The support networks included either just the spouse or the spouse and other people. Social relationships broke down a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 40 publications
4
46
0
16
Order By: Relevance
“…Authors have found that while many FILM may be surrounded by others on the street and in social and kinship networks, they often experience a lack of opportunity or comfort to talk openly about issues that affect them most, leaving them to deal with symptoms of anxiety and depression alone (Muñoz-Laboy et al, 2012). The importance of social networks and support for men experiencing depression and in the aftermath of loss is well-documented (Aho, Tarkka, Astedt-Kurki, & Kaunonen, 2009; Watkins, 2012), as are the negative mental health consequences for men whose social bonds have deteriorated (Oliffe, Han, Ogrodniczuk, Phillips, & Roy, 2011). …”
mentioning
confidence: 99%
“…Authors have found that while many FILM may be surrounded by others on the street and in social and kinship networks, they often experience a lack of opportunity or comfort to talk openly about issues that affect them most, leaving them to deal with symptoms of anxiety and depression alone (Muñoz-Laboy et al, 2012). The importance of social networks and support for men experiencing depression and in the aftermath of loss is well-documented (Aho, Tarkka, Astedt-Kurki, & Kaunonen, 2009; Watkins, 2012), as are the negative mental health consequences for men whose social bonds have deteriorated (Oliffe, Han, Ogrodniczuk, Phillips, & Roy, 2011). …”
mentioning
confidence: 99%
“…Furthermore, informational support from secondary care professionals was evaluated as insufficient and many parents This contact should be initiated by the professional. In line with the results of other studies, parents indicate that they would appreciate the provision of more support and follow-up appointments or contacts with a professional after the death of their child [14,150].…”
Section: Discussionsupporting
confidence: 73%
“…Parents value health professionals and others who approach them with empathy, kindness and respect. They also value professionals when they listen and communicate well and offer support before and after the death of a child [14,140,149,150]. According to parents, support should be offered on an individual basis and may vary in intensity depending on the family needs [140].…”
Section: Introductionmentioning
confidence: 99%
“…Esses sintomas são caracterizados por inibição comportamental, que contribui consideravelmente para a deterioração do funcionamento social. Embotamento e retraimento social se expressam no inventário de habilidades sociais contribuindo para a formação de escores inferiores, o que torna este achado, de certa forma, previsível 33,34,35 . O falecimento de filhos é descrito como um evento capaz de gerar queixas emocionais e repercussões de cunho comportamental duradouras.…”
Section: Discussionunclassified